Ultraviolet A1 Phototherapy for Fibrosing Conditions - Gambichler, Thilo; Schmitz, Lutz (Frontiers in Medicine, 2018)
Ultraviolet A1 (UV-A1) phototherapy is a specific phototherapeutic modality characterized by a selective UV spectrum ranging from 340 nm to 400 nm. UV-A1 includes distinct modes of action qualifying this method for therapy of a variety of conditions, in particular fibrosing skin diseases. Concerning efficacy UV-A1 phototherapy in fibrosing conditions, the best evidence obtained from randomised controlled trials exists for localized scleroderma. Moreover, fibrosing disorders such as systemic sclerosis, lichen sclerosus, and graft-versus-host disease can be treated successfully by means of UV-A1. Regarding the optimal dosage regimen medium-dose UV-A1 seems to be linked to the best benefit/risk ratio. Possible acute adverse events of UV-A1 phototherapy include erythema and provocation of photodermatoses. Skin ageing and skin cancer formation belong to the chronic adverse events that may occur after long-term UV-A1 phototherapy.